Engineering education challenges and strengths: reflecting on key-stakeholder's perspectives - Ferreira, Carla; Gabriel, Bárbara; Valente, Robertt; Figueiredo, Cláudia (Frontiers in Education, 2024)
We live in a society in constant scientific and technological change, where engineering education is required to develop the competences needed for future engineers to be able to respond to the complex and interdisciplinary problems that arise from this. It is no longer enough just to provide updated scientific and technological training to students, but it is also required to articulate the needs of society with the design of the curriculum and the expectations of the different stakeholders. The present paper's goal is to present the perceptions about engineering education through the lens of different institutional stakeholders, following a qualitative design study, through semi-structured interviews with seven key-stakeholders representing different scientific and professional institutions. These interviewees play an important role in the definition of guidelines for the engineering profession and in (re)thinking curricula reflecting the interaction with society, training and research. In this sense, it aims to explore the following objectives: (i) to know the perception about the profession, the profile of engineers and the engineering curricula; (ii) to identify the challenges posed to engineers in the job market and in society, today and in the future; and (iii) to reflect on a desirable profile to be attained by engineering students at the end of their Higher Education path. From the interviewees' perspective, competences development effectively involves learning approaches that realise which problem-solving strategies, concepts and capacities for social action should be developed in students, which are not restricted to disciplinary or specific content, but which allow (de)constructing curricula that reflect the different needs of society. In fact, as well as including the point of view of renowned international associations, this article reinforces the idea that the integration of science, technology, engineering and maths (STEM) into curricula is not only a challenge, but also a growing and inevitable phenomenon in response to society's needs. The curriculum, the competences to be privileged, the importance of interdisciplinarity, and the contribution of STEM and STEAM approaches from an integrated engineering perspective are interpreted as difficulties but also the target opportunities.